2013
DOI: 10.1130/g33735.1
|View full text |Cite
|
Sign up to set email alerts
|

Slope and climate variability control of erosion in the Andes of central Chile

Abstract: Artículo de publicación ISIClimate and topography control millennial-scale mountain erosion, but their relative impacts remain matters of debate. Confl icting results may be explained by the infl uence of the erosion threshold and daily variability of runoff on long-term erosion. However, there is a lack of data documenting these erosion factors. Here we report suspended-load measurements, derived decennial erosion rates, and 10Be-derived millennial erosion rates along an exceptional climatic gradient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 33 publications
15
106
1
1
Order By: Relevance
“…In tectonically active and previously glaciated mountain ranges there are three common orogenic processes that are most often suggested to dominate Holocene erosion rate patterns: climate gradients (Carretier et al, 2013;Olen et al, 2016), glacial modification of the landscape (Moon et al, 2011;Glotzbach et al, 2013), and patterns of tectonic rock uplift (Scherler et al, 2013;Godard et al, 2014;Adams et al, 2016). In the following we explore the relevance and applicability of these explanations to our dataset.…”
Section: Orogenic Processes Governing Erosion Ratesmentioning
confidence: 99%
“…In tectonically active and previously glaciated mountain ranges there are three common orogenic processes that are most often suggested to dominate Holocene erosion rate patterns: climate gradients (Carretier et al, 2013;Olen et al, 2016), glacial modification of the landscape (Moon et al, 2011;Glotzbach et al, 2013), and patterns of tectonic rock uplift (Scherler et al, 2013;Godard et al, 2014;Adams et al, 2016). In the following we explore the relevance and applicability of these explanations to our dataset.…”
Section: Orogenic Processes Governing Erosion Ratesmentioning
confidence: 99%
“…As rare and strong erosive events represent the most important contribution to the long-term erosion of the arid Western Cordillera (Carretier et al, 2013), we propose that events like the Chuquibamba landslide contribute significantly to the long-term erosion of the western escarpment of the Andes. We thus suggest a strong regional tectonic and climatic control of the long-term erosion of the arid western Andean front.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Altiplano has been the target of many paleoclimatic investigations (Thompson et al, 1998(Thompson et al, , 2000Cross et al, 2001;Baker et al, 2001;Placzek et al, 2006Placzek et al, , 2013 that highlighted climate fluctuations for the last 130 kyr. Steffen et al (2009Steffen et al ( , 2010, Carretier et al (2013) and Bekaddour et al (2014) highlighted the contribution of these wet climatic events to mass transport in major canyons from the Altiplano to the Pacific coast. In contrast, McPhillips et al (2014) observed that the landslide frequency appears to have not changed during the Quaternary and thus questioned the impact of the climatic fluctuations on landsliding and erosion rate.…”
Section: Geologic and Climatic Setting Of Chuquibamba Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bookhagen et al, 2005), although their relationship to other environmental parameters, such as vegetation cover, remains disputed (e.g. Istanbulluoglu and Bras, 2005;Carretier et al, 2013;Dosseto and Schaller, 2016). Our current model does not to take such processes into account.…”
Section: Impact Of Climate Changementioning
confidence: 99%